Lexical Definitions of Some Performative Verbs - Hlebec, Boris (Studia Anglica Posnaniensia, 2015)
The author upholds Anna Wierzbicka’s opinion that unless strict scientific definitions of performatives are reached, no successful classification of these verbs can be made. The article compares definitions of the verb elect and four performative verbs (appoint, declare, excommunicate and pronounce) as presented in four English dictionaries, as well as in the form of Wierzbicka’s explicatives and the author’s formulations reached by means of the collocational method. This method seeks to gain a realistic insight into the semantic structure of lexemes because most metalinguistic elements are drawn from facts offered by the language itself. The definitions of the performative verbs, like of any other verb, can be marshalled by combining and incorporating semantic definitions of the collocating grammar words and constructions. The latter task is done by extracting the common content of the grammar words and constructions in the relevant meanings as appearing in collocations of their own. The same procedure is carried out for the noun collocates occurring in the subject and object slots of the verbs in question. The performative force within this small lexical field manifests gradation, depending on the presence of a person in authority.